Genetic External Characteristics of Tukong: Indonesian Rumpless Indigenous Chicken - Tribudi, Yuli Arif; Nurgiartiningsih, Veronica Margaretha Ani; Ulfah, Maria; Sari, Aprilianna Putri Zahara Nafsina Luvita; Hariyono, Dwi Nur Happy; Sitaresmi, Pradita Iustitia; Crooijmans, Richard PMA; Natsir, Muhammad Halim; Gusmalawati, Dwi; Ibrahim, Alek (Bogor Agricultural University, Indonesia, 2025)
Tukong chicken, also known as rumpless chicken due to the absence of a tailbone, is one of the indigenous chicken breeds in Indonesia currently at risk of extinction. Due to its scarcity, genetic information on the Tukong chicken remains limited, and its potential has not been fully explored. Therefore, this study aimed to determine the genetic external characteristics of the Tukong chickens. Data were collected from 205 chickens (52 males; 153 females) raised in Landak and Bengkayang Regency, West Kalimantan. The varieties are based on feather color, plumage color, feather pattern, feather flicker, comb shape, and shank color. The data were used to analyze the rate of the original gene, the frequency of autosomal genes, sex-linked genes, feather pattern, introgression rate, gene frequency, and expected heterozygosity. The majority of the Tukong chickens had colored feathers (88.78%), columbian feather type (47.80%), plain feather pattern (61.46%), silver feather flicker (54.63%), yellow-white shank (62.44%), and pea comb (77.07%), which were controlled by ii, ee, bb, SS, IdId, and P_ genes, respectively. The introgression rate from exotic breeds into Tukong chicken is 53.2%, with the original gene at 46.8%, while the average expected heterozygosity was 0.416±0.025, indicating a high level of genetic diversity of the traits. This observed variation in qualitative morphological characteristics might benefit both the conservation and utilization of the Tukong chicken.